2018
DOI: 10.1038/s41598-018-25214-0
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study with IBAT inhibitor A4250 for the treatment of cholestatic pruritus in primary biliary cholangitis

Abstract: Pruritus is a common complication of cholestatic liver diseases. Inhibition of the ileal bile acid transporter (IBAT/ASBT) may emerge as treatment option. Our aim was to assess tolerability and effect on pruritus of the selective IBAT inhibitor A4250 in patients with primary biliary cholangitis (PBC). Ten patients with PBC and bile acid sequestrant treatment of cholestatic pruritus were after a two-week wash out of the bile acid sequestrant treated with either 0.75 mg (n = 4) or 1.5 mg (n = 5) of A4250 for fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 24 publications
(26 reference statements)
0
51
0
Order By: Relevance
“…The treatment of pruritus in PBC is challenging because of the limited efficacy and poor tolerability of currently available drugs and lack of effective new therapies. Ileal bile acid transporter (IBAT) inhibitor agents are emerging as potential novel therapy for pruritus in PBC . Recently, we investigated GSK2330672, a novel, selective human IBAT inhibitor in a phase 2a, randomised controlled trial (RCT) and showed that PBC patients with pruritus receiving 2 weeks of oral treatment with GSK2330672 had significant improvement in their pruritus compared to placebo …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment of pruritus in PBC is challenging because of the limited efficacy and poor tolerability of currently available drugs and lack of effective new therapies. Ileal bile acid transporter (IBAT) inhibitor agents are emerging as potential novel therapy for pruritus in PBC . Recently, we investigated GSK2330672, a novel, selective human IBAT inhibitor in a phase 2a, randomised controlled trial (RCT) and showed that PBC patients with pruritus receiving 2 weeks of oral treatment with GSK2330672 had significant improvement in their pruritus compared to placebo …”
Section: Introductionmentioning
confidence: 99%
“…Ileal bile acid transporter (IBAT) inhibitor agents are emerging as potential novel therapy for pruritus in PBC. [7][8][9][10] Recently, we investigated GSK2330672, a novel, selective human IBAT inhibitor in a phase 2a, randomised controlled trial (RCT) and showed that PBC patients with pruritus receiving 2 weeks of oral treatment with GSK2330672 had significant improvement in their pruritus compared to placebo. 11 Over the years, metabonomics has been applied to study the metabolic signatures in a variety of liver diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Only four patients finished the 4-week protocol and also reported a decrease in pruritic intensity. Five patients stopped their participation in the study early due to diarrhea and abdominal discomfort [27]. Odevixibat has also been investigated in pediatric cholestasis syndromes in a multiple dose (10-200-μg/kg bodyweight/day), open-label trial.…”
Section: Ileal Bile Acid Transporter Inhibitorsmentioning
confidence: 99%
“…to increased BA deposition (75). IBAT/ASBT inhibitors are potential therapeutic candidates for this detrimental symptom (76). Pilot studies conducted with various synthetic IBAT/ASBT inhibitors have demonstrated variable results.…”
Section: Bile Acid Receptor/transporter Agonists and Antagonistsmentioning
confidence: 99%